Taking care of yourself and your family : a resource book for good mental health - Ashfield, John.; Country Health SA; Beyondblue (Organisation) (Norwood, S. Aust. : Peacock Publications for Beyondblue, the National Depression Initiative, 2010)
This easy-to-understand book deals with a whole range of subjects of importance to people concerned with taking care of their mental health. Though it has been written with rural people in mind, it will be of assistance to those living in the city.
Introduction -- Depression -- Anxiety -- Disturbing thoughts -- Recovery from trauma -- Insomnia -- Conflict -- Anger -- Stress -- Relationship violence -- Alcohol -- Substances and mental health -- Grief -- Key services and resources -- Perinatal depression and anxiety -- Chronic illness and mental helath -- Aboriginal and Torres Strait Islanders -- Young people -- Sources used in the preparation of this book.
Title from title screen, viewed 18 Aug. 2011.
"Supported by beyondblue: the national depression initiative".
"Government of South Australia, Country Health SA".
"March 2010" -- T.p. verso.
Includes bibliographical references (p. 320-322)
Also available in print.
Keywords: Self-care, Health -- Popular works; Stress management -- Popular works; Mental health promotion -- South Australia -- Mid North Region